Elucidating the source of bloodstream Trypanosoma brucei mitochondrial ATP - Husová, Michaela (Jihočeská univerzita, 2021)
For decades, it has been assumed that the reduced function and structure of the bloodstream form Trypanosoma brucei mitochondrion renders it a strictly ATP consuming organelle. Emerging evidence from refocused studies suggest that the bloodstream mitochondrion retains complex bioenergetic pathways that allow the parasite to adapt to various environments. This thesis is focused on the source of bloodstream mitochondrial ATP, with a special emphasis on the role of succinyl-CoA to produce ATP via mitochondrial substrate phosphorylation. We will also discuss alternative bioenergetic pathways present in this life stage of a human pathogen.
Elucidating the source of bloodstream Trypanosoma brucei mitochondrial ATP
Keywords: Trypanosoma brucei; mitochondria; bioenergetics; substrate phosphorylation; succinyl coenzyme A; Trypanosoma brucei; mitochondria; bioenergetics; substrate phosphorylation; succinyl coenzyme A